2018
DOI: 10.7150/jca.25542
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effects of COL1A2 on colorectal cancer cell proliferation, migration, and invasion

Abstract: Purpose: Collagen type I alpha 2 chain (COL1A2) has been shown to participate in the development of various human malignancies. However, the role of COL1A2 in human colorectal cancer (CRC) remains unknown. This study investigated the expression pattern of COL1A2 in primary CRC tissues as well as the correlation of COL1A2 expression with clinicopathological features and prognosis of CRC. The function of COL1A2 in CRC cell proliferation, migration, and invasion as well as the possible mechanisms were also examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 37 publications
2
36
0
3
Order By: Relevance
“…COL1A2 is signi cantly down-regulated in colorectal cancer (CRC) tissues, and COL1A2 mRNA expression levels are related to tumor differentiation, invasion, and lymph node metastasis in CRC patients. COL1A2 overexpression inhibited CRC cell line proliferation, migration, and invasion [34]. COL3A1 expression is elevated in CRC tissues and cells.…”
Section: Expression Of Lgals1 and Its Diagnostic Value In Escamentioning
confidence: 89%
“…COL1A2 is signi cantly down-regulated in colorectal cancer (CRC) tissues, and COL1A2 mRNA expression levels are related to tumor differentiation, invasion, and lymph node metastasis in CRC patients. COL1A2 overexpression inhibited CRC cell line proliferation, migration, and invasion [34]. COL3A1 expression is elevated in CRC tissues and cells.…”
Section: Expression Of Lgals1 and Its Diagnostic Value In Escamentioning
confidence: 89%
“…In bladder and colorectal cancer, COL1A2 was significantly downregulated and mainly plays an anticarcinogenic role in tumor development. [ 42 , 43 ] However, in other malignancies such as ovarian cancer, pancreatic cancer, and head and neck cancer, overexpressed COL1A2 was found to promote tumor cell invasion and migration. [ 44 , 45 ] Thus, the unique roles of COL1A2 in various cancers may be partially attributed to specific genetic characteristics of the different malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…COL1A1 can be used as a new therapeutic marker and a target for hepatocellular carcinogenesis (Ma et al, 2019). Another study demonstrated that COL1A2 may affect proliferation, migration, and invasion of colorectal cancer cells (Yu et al, 2018). Omar Ret al, reported that COL1A2 affects cell migration of fibrosarcoma and chondrosarcoma by acting on TBX3 (Omar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%